Comparison of anthropometric-based equations for estimation of body fat percentage in a normal-weight and overweight female cohort: validation via air-displacement plethysmography. Issue 3 (16th April 2014) - Temple, Derry; Denis, Romain; Walsh, Marianne C; Dicker, Patrick; Byrne, Annette T
Abstract Objective To evaluate the accuracy of the most commonly used anthropometric-based equations in the estimation of percentage body fat (%BF) in both normal-weight and overweight women using air-displacement plethysmography (ADP) as the criterion measure. Design A comparative study in which the equations of Durnin and Womersley (1974; DW) and Jackson, Pollock and Ward (1980) at three, four and seven sites (JPW3, JPW4 and JPW7) were validated against ADP in three groups. Group 1 included all participants, group 2 included participants with a BMI<25·0 kg/m2 and group 3 included participants with a BMI≥25·0 kg/m2. Setting Human Performance Laboratory, Institute for Sport and Health, University College Dublin, Republic of Ireland. Subjects Forty-three female participants aged between 18 and 55 years. Results In all three groups, the %BF values estimated from the DW equation were closer to the criterion measure (i.e. ADP) than those estimated from the other equations. Of the three JPW equations, JPW3 provided the most accurate estimation of %BF when compared with ADP in all three groups. Conclusion In comparison to ADP, these findings suggest that the DW equation is the most accurate anthropometric method for the estimation of %BF in both normal-weight and overweight females.